The Relationship Between Family Support and The Quality of Life of Cancer Patients Undergoing Chemotherapy at Santa Elisabeth Hospital Medan - Sinurat, Samfriati; Pane, Jagentar; Indra Hizkia P; Panjaitan, Lasria (Jurnal Anestesi, 2026)
A decrease in quality of life among cancer patients undergoing chemotherapy often involves psychological and emotional problems such as confusion, sadness, anxiety, helplessness, fear of death, concerns about disclosing illness to family members, reduced self-esteem, disturbed body image, and loss of hope, which reflect a diminished sense of meaning in life. In this condition, strong family involvement and support are essential to help patients cope with the physical and emotional burden of chemotherapy and to improve their overall quality of life. This study aims to determine the relationship between family support and the quality of life of cancer patients undergoing chemotherapy at Santa Elisabeth Hospital Medan in 2024. The research used a quantitative method with a cross-sectional design. A total of 72 respondents were selected using accidental sampling. Data were collected through questionnaires measuring family support and quality of life. The results showed that most respondents received good family support, with 37 respondents (51.4%), while the quality of life was mostly in the adequate category, with 34 respondents (47.2%). Statistical analysis using the Spearman rank correlation test showed a significance value of p = 0.002 (p < 0.05) and a correlation coefficient of r = 0.731, indicating a strong positive relationship between family support and quality of life. These findings confirm that better family support is associated with higher quality of life among cancer patients undergoing chemotherapy and highlight the importance of strengthening coping strategies and psychosocial support.